High-level area and power estimation for VLSI circuits - Nemani, M.; Najm, F.N. (IEEE transactions on computer-aided design of integrated circuits and systems, 1999)
High-level power estimation, when given only a high-level design specification such as a functional or register-transfer level (RTL) description, requires high-level estimation of the circuit average activity and total capacitance. Considering that total capacitance is related to circuit area, this paper addresses the problem of computing the "area complexity" of multi-output combinational logic given only their functional description, i.e., Boolean equations, where area complexity refers to the number of gates required for an optimal multilevel implementation of the combinational logic. The proposed area model is based on transforming the multi-output Boolean function description into an equivalent single output function. The area model is empirical and results demonstrating its feasibility and utility are presented. Also, a methodology for converting the gate count estimates, obtained from the area model, into capacitance estimates is presented. High-level power estimates based on the total capacitance estimates and average activity estimates are also presented.